Etika Bisnis Islam dalam Implementasi Teknologi Neuromarketing pada Strategi Pemasaran - Kisti Nur Aliyah (Universitas Islam Lamongan, 2020)
Over time, marketing activities are also developing very rapidly. The latest theory that currently carried out by the concept of neuromarketing biometrics, which can influence consumer psychology, so consumers are interested in buying the products, goods, or services offered. Brain imaging techniques are used in biometrics neuromarketing research using fMRI, EEG, eye tracking, and others. The purpose of this research is to find and describe the urgency of using neuromarketing biometrics technology in marketing strategies. Biometric neuromarketing implementation analyzes marketing strategies and also analyze perspective of basic principles of Islamic business ethics towards using technology and biometrics neuromarketing implementation. This research is a type of qualitative research with a library research approach. Data obtained from journals that discuss the use of these technologies, then analyzed using interactive analysis techniques. The results show that neuromarketing biometrics is a useful technology in helping marketers determine marketing strategies because by using this technology, marketers get valuable internal data in the unconscious consumer brain. But in its implementation, there are deviations from the basic principles of Islamic business ethics, including the use of psychological discounts, sense of urgency, and fraud in advertising. While in the use of technology, three things that are highlighted, including the issue of conquering the mind and using it in advertising interests, the problem of violating the free will of consumers, and the problem of violating federal guidelines using human subjects. It hopes that future researchers will be a focus on the study of Islamic business ethics on the use of neuromarketing biometrics technology. Keywords: neuromarketing; Islamic business ethics